Optically clear silicone acrylate adhesive composition

By using a composition containing an organopolysiloxane resin containing a high content of ‘T’ siloxane unit and a specific (meth)acrylate component, the shrinkage problem of the photocurable optically transparent adhesive during curing is solved, high transparency and strong adhesion are achieved, and the use of plasticizers is avoided.

CN119562999APending Publication Date: 2025-03-04DOW SILICONES CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380054151.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-08-08
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing photocurable optically transparent adhesives are prone to shrink when cured, resulting in unstable bonding. Plasticizers are often required to reduce shrinkage, but the residue of plasticizers is undesirable.

Method used

Using an organopolysiloxane resin containing at least 50 mole% of the ‘T’ siloxane units as the adhesion promoter, combined with a specific proportion of the (meth)acrylate components, a crosslinking agent and a photoradical initiator, the formed composition can reduce shrinkage when cured without using a plasticizer.

Benefits of technology

A shrinkage of less than 8% upon curing is achieved while maintaining high transparency, appropriate viscosity and strong peel adhesion, suitable for inkjet printing and optically transparent adhesive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244618960000151
    Figure BDA0005244618960000151
  • Figure BDA0005244618960000161
    Figure BDA0005244618960000161
  • Figure BDA0005244618960000171
    Figure BDA0005244618960000171
Patent Text Reader

Abstract

The present invention provides a composition comprising: (a) 10% by mass to 90% by mass of an organopolysiloxane resin; (b) from 10% by mass to 90% by mass of a (meth) acrylate component consisting of (i) at least one monofunctional (meth) acrylate containing ether groups and / or hydroxyl groups; and optionally (ii) at least one monofunctional (meth) acrylate containing an alkyl group and not containing an ether group and a hydroxyl group; wherein the molar ratio of (ii) to (i) is in the range of from 0: 1 to 22: 1, and wherein when the (meth) acrylate component comprises a hydroxyl group-containing monofunctional (meth) acrylate, the hydroxyl group-containing monofunctional (meth) acrylate has a hydroxyl group-containing hydroxyl group-containing monofunctional (meth) acrylate; if so, it further comprises as part of component (i) at least one monofunctional (meth) acrylate containing ether groups and / or as part of component (ii) a monofunctional (meth) acrylate containing alkyl groups and not containing ether groups and hydroxyl groups; (c) from 0.11% by mass to 11% by mass of a cross-linking agent; and (d) 0.1% to 10% by mass of a photo-radical initiator; wherein the mass percent is relative to the combined mass of component (a) to component (c).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to curable silicone-based compositions that cure upon exposure to ultraviolet light to form optically clear adhesive materials.

[0002] introduction

[0003] Photocurable optically clear adhesives, particularly photocurable liquid optically clear adhesives, can be applied to optical bonding of electronic devices such as optical displays. Photocurable optically clear adhesives optically couple elements in display applications, where the optically coupled elements may include display panels, glass plates, touch panels, diffusers, stiffness compensators, heaters, and flexible films such as polarizers and retarders.

[0004] (Meth)acrylate materials are common in photocurable adhesives. However, when (meth)acrylate compositions are cured, particularly when there is a large amount of acrylate monomers to keep the composition viscosity low enough to facilitate inkjet printing of the composition, (meth)acrylate compositions tend to undergo shrinkage. Shrinkage corresponds to dimensional instability, which is undesirable in adhesives because it can lead to pulling apart or delamination from the elements to which the adhesive is to be bonded. It is known that adding plasticizers to (meth)acrylate compositions can reduce the shrinkage of the composition during curing, but the composition will then retain residual plasticizer and this is generally undesirable. Therefore, it is desirable to avoid the use of plasticizers.

[0005] The art of photocurable optically clear adhesives will be advanced to identify a (meth)acrylate composition for use as a photocurable adhesive having a viscosity in the range of 10 millipascals*seconds (MPa*s) to 100,000 MPa*s at 25 degrees Celsius (° C.), and preferably a viscosity of at least 10 MPa*s at 25° C., while having a viscosity of 50 MPa*s or less at 60° C., so that it is suitable for inkjet applications, and after photocuring having a transparency at 550 nanometers through a one millimeter thick film of the cured composition of greater than 90%, a shear storage modulus in the range of one kilopascal (kPa) to 5,000 kPa at one hertz and 1% shear rate at 25° C. to 80° C., a peel adhesion to polyethylene terephthalate (PET) greater than 38.6 Newtons / meter (greater than 100 grams-force / inch), and undergoing less than 8% shrinkage upon curing as described herein below. It would be particularly desirable to achieve these properties without the use of plasticizers. Summary of the invention

[0006] The present invention solves the problem of providing a photocurable optically clear adhesive in the form of a (meth)acrylate composition having a viscosity in the range of 10 millipascals*seconds (MPa*s) to 100,000 MPa*s at 25 degrees Celsius (°C), and may even have a viscosity of at least 10 MPa*s at 25°C, while having a viscosity of 50 MPa*s or less at 60°C, so that it is suitable for inkjet applications, and after photocuring has a transparency of greater than 90% at 550 nanometers through a one millimeter thick film of the cured composition, a storage modulus in the range of one kilopascal (kPa) to 5000 kPa at one hertz and 1% shear rate at 25°C to 80°C, a peel adhesion to PET of greater than 38.6 Newtons / meter (greater than 100 grams-force / inch), and undergoes less than 8% shrinkage when cured as described herein below. It has been found that the compositions of the present invention can achieve these properties without the use of plasticizers. It has also been found that the compositions of the present invention can be inkjet dispensable.

[0007] The present invention is the result of the surprising and unexpected discovery that the inclusion of an organopolysiloxane resin containing at least 50 mole percent (mol%) of "T" siloxane units in a (meth)acrylate photocurable composition of the present invention, wherein the molar ratio of alkyl to aryl groups in the organopolysiloxane resin is in the range of 0:1 to 4:1 and the concentration of hydroxyl and alkoxy groups (collectively referred to as "OZ" groups) bonded to silicon atoms in the organopolysiloxane is in the range of 0 mol % to 100 mol % based on the number of moles of the organopolysiloxane resin, is used as an adhesion promoter and can solve the above-mentioned problems. It is particularly surprising that the organopolysiloxane resin reduces shrinkage of the composition upon curing.

[0008] In a first aspect, the present invention is a composition comprising: (a) 10 to 90% by mass of an organopolysiloxane containing at least 50 mol% of T siloxane units, wherein the molar ratio of alkyl groups to aryl groups in the organopolysiloxane is in the range of 0:1 to 4:1; (b) 10 to 90% by mass of a (meth)acrylate component consisting of: (i) at least one monofunctional (meth)acrylate containing ether groups and / or hydroxyl groups; and optionally (ii) at least one monofunctional (meth)acrylate containing alkyl groups and free of ether groups and hydroxyl groups; wherein the molar ratio of (ii) to (i) is in the range of 0:1 to 22:1, and wherein when the (meth)acrylate component is When the meth)acrylate component contains a monofunctional (meth)acrylate containing a hydroxyl group, it also contains at least one monofunctional (meth)acrylate containing an ether group as part of component (i) and / or a monofunctional (meth)acrylate containing an alkyl group and not containing an ether group and a hydroxyl group as part of component (ii); (c). 1% to 11% by mass of a crosslinker having an average of at least two ethylenically unsaturated double bonds per molecule; and (d). 1% to 10% by mass of a photoradical initiator; wherein the mass percentages are relative to the combined mass of components (a) to (c), and wherein the mass percentages of components (a) to (c) add up to 100% by mass.

[0009] In a second aspect, the present invention is a method comprising using the composition of the first aspect as an adhesive, the method comprising the steps of applying the composition to a first object, and then applying a second object to the composition so that the composition is sandwiched between and in contact with the first object and the second object.

[0010] The compositions of the present invention are useful as optically clear adhesives. DETAILED DESCRIPTION

[0011] When a test method number is not used to indicate a date, the test method refers to the most current test method as of the priority date of this document. Reference to a test method includes reference to both the testing association and the test method number. The following test method abbreviations and identifiers apply herein: ASTM refers to the American Society for Testing and Materials; EN refers to European Standards; DIN refers to the German Institute for Standardization; JIS refers to Japanese Industrial Standards, and ISO refers to the International Standards Organization.

[0012] Products identified by their trade names refer to compositions available under those trade names on the priority date of this document.

[0013] "Plurality" means two or more. "And / or" means "and, or as an alternative". All ranges are inclusive unless otherwise indicated. Identification of a material by a trademark or trade name means that the material has the composition sold under that trademark or trade name on the priority date of this document.

[0014] The general term "C x-y ”, “C x -C y ”, “Cx to Cy” and “Cx-Cy” are interchangeable in the context of chemical structures and refer to having x to y carbon atoms in the chemical structure.

[0015] When referring to polymers, molecular weight herein refers to weight average molecular weight (Mw). A Waters 2695 Separations Module with a Waters 2487 Ultraviolet (UV) detector was used, and three STYRAGEL TM HR column (7.8 mm by 300 mm, molecular weight separation range 100 to 4,000,000) and STYRAGEL with THF TM The Mw of the polymer is determined using gel permeation chromatography (GPC) with a guard column (7.8 mm by 200 mm) as the column. STYRAGEL is a trademark of Millipore Corporation. The sample is prepared as a 0.5 mass percent (mass %) solution in toluene and filtered through a 0.45 micron polytetrafluoroethylene injection filter. A flow rate of one milliliter per minute, a column and detector temperature of 35 degrees Celsius (° C.), a syringe volume of 100 microliters, and a run time of 60 minutes are used. Mw is calculated relative to a linear polystyrene standard covering a molecular weight range of 580 to 2,610,000.

[0016] "(Meth)acryloyloxy" refers to acryloyloxy and / or methacryloxy. Acryloyloxy has the chemical structure: H2C=CH-C(O)O-. Methacryloxy has the chemical structure: H2C=C(CH3)-C(O)O-.

[0017] "Siloxane" refers to a molecule containing at least one siloxane (Si-O-Si) bond. In this article, "siloxane" can be a "polysiloxane" having multiple siloxane bonds or a siloxane having only one siloxane bond. When a siloxane having more than one siloxane bond is intended, the term "polysiloxane" is used. Polysiloxanes can have chain, ring, ladder, and three-dimensional network structures.

[0018] Polysiloxanes contain multiple siloxane units linked together by siloxane bonds. Siloxane units can be characterized by the designations M, D, T, or Q. There are two generally accepted usages of the MDTQ nomenclature: the GE method and the NMR method. The usage herein is based on the following NMR method. Unless otherwise expressly stated, "M" corresponds to R3SiO 1 / 2 Siloxane unit. "D" corresponds to R2SiO 2 / 2 and R2(OZ)SiO 1 / 2 Combination of siloxane units. "T" corresponds to RSiO 3 / 2 、R(OZ)SiO 2 / 2 and R(OZ)2SiO 1 / 2 The combination of siloxane units. "Q" corresponds to (OZ)3SiO 1 / 2 、(OZ)2SiO 2 / 2 、(OZ)SiO 3 / 2 and SiO 4 / 2 A combination of siloxane units. "R" is independently selected from a hydrocarbon group at each occurrence, and can be an alkyl group or an aryl group. Preferably, R is selected from the group consisting of a C1-C8 alkyl group (such as methyl, ethyl, propyl, methyl, butyl, pentyl, hexyl, heptyl and octyl) and a C6-C20 aryl group (including phenyl and benzyl). "OZ" is -OH or -OR, wherein R is as described above.

[0019] It is worth noting that oxygen atoms with multiple "1 / 2" subscripts are oxygens of siloxane bonds shared with silicon atoms of two siloxane units (including one of the subject siloxane units). The number of subscripts indicates how many shared oxygen atoms are connected to the silicon atom. For example, SiO 3 / 2 Has three siloxane-bonded oxygen atoms.

[0020] M, D, and T notations may include superscripts indicating what R groups are bonded to the silicon atoms of the siloxane units. If superscript notations are not used, it is assumed that the R groups are all methyl. For example, T Pr refers to a T unit in which the R group is n-propyl. Ph The unit is a T unit in which the R group is a phenyl group. MA The unit is a T unit in which the R group is a (meth)acryloxypropyl group. Me,Me and D Me 2 each refers to a D unit having two methyl R groups on the silicon atom. Ph,Me and D Ph Both refer to D units having one phenyl R group and one methyl R group on the silicon atom. Ph,Ph and D Ph2 All refer to D units with two phenyl R groups on the silicon atom. Me,Me,Me and M Me3All refer to M units having three methyl R groups on the silicon atom.

[0021] The chemical formula names of polysiloxanes using the M, D, T, Q nomenclature generally have a subscript associated with the siloxane unit name, which unit name may refer to the average molar ratio of the siloxane unit relative to all siloxane units in the molecule or the average number of associated siloxane units in the molecule. When the subscript associated with a siloxane unit is greater than or equal to one, then the subscript refers to the average number of those siloxane units in the molecule. When the subscript associated with a siloxane unit is less than one, then the subscript refers to the average molar ratio of the siloxane unit relative to the number of moles of all siloxane units in the molecule. The absence of a subscript means that the subscript value is one.

[0022] "Organopolysiloxane" refers to a polysiloxane having at least one organic group bonded to a silicon atom of the polysiloxane.

[0023] "Optically clear" or "optically transparent" refers to a material having a transmittance of at least 90% at a wavelength of 550 nanometers when measured through a 1.0 millimeter thick film of the material. The transmittance is measured as described in the Examples section below.

[0024] The composition of the present invention comprises: (a) an organopolysiloxane resin; (b) a (meth)acrylate component; (c) a crosslinking agent; and (d) a photoradical initiator.

[0025] The organopolysiloxane resin contains at least 50 mol% of "T" siloxane units and may contain 50 mol% or more, 60 mol% or more, 70 mol% or more, or even 80 mol% or more, while typically containing 100 mol% or less, 90 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, or even 60 mol% or less of T siloxane units, based on all siloxane units in the organopolysiloxane resin.

[0026] The molar ratio of alkyl to aryl groups in the organopolysiloxane resin is 0:1 or greater, and can be 0.1:1 or greater, 0.2:1 or greater, 0.4:21 or greater, 0.7:1 or greater, 1:1 or greater, 1.2:1 or greater, 1.5:1 or greater, 2.0:1 or greater, 2.5:1 or greater, 3.0:1 or greater, and even 3.5:1 or greater, while typically being 4.0:1 or less, and can be 3.5:1 or less, 3.0:1 or less, 2.5:1 or less; 2:1 or less, 1.5:1 or less, 1.2:1 or less, 1.1:1 or less, 1.0:1 or less; 0.7:1 or less, 0.4:1 or less, 0.2:1 or less, or even 0.1:1 or less. Desirably, alkyl is independently selected at each occurrence from C1-C8 alkyl, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl and octyl. Desirably, aryl is selected from C6 to C20 aryl, including aryl and phenyl.

[0027] Desirably, based on the mole number of the organopolysiloxane resin, the OZ concentration of the organopolysiloxane resin is 0mol% or greater, and can be 5mol% or greater, 10mol% or greater, 20mol% or greater, 30mol% or greater, 40mol% or greater, 50mol% or greater, 50mol% or greater, 60mol% or greater, 70mol% or greater, 80mol% or greater, even 90mol% or greater, while typically 100mol% or less, and can be 90mol% or less, 80mol% or less, 70mol% or greater, 60mol% or greater, 50mol% or greater, 40mol% or greater, 30mol% or less, 20mol% or less, even 10mol% or less. Desirably, the OZ group is a hydroxyl group.

[0028] use 29 4. 13 C and 1 The molar ratio of alkyl to aryl groups and the OZ concentration in the organopolysiloxane resin are determined by H NMR spectroscopy (see, e.g., The Analytical Chemistry of Silicones, Smith, A. Lee, ed., John Wiley & Sons: New York, 1991, pp. 347 et seq.).

[0029] The organopolysiloxane resin may have an average chemical formula (I):

[0030] M a D b T c Q d(I)

[0031] in:

[0032] Subscript a is the molar ratio of the M siloxane units relative to all siloxane units in the organopolysiloxane resin, and has an average value of 0 or more, and may have an average value of 0.10 or more, 0.15 or more, 0.20 or more, or even 0.25 or more, while typically having an average value of 0.35 or less, and may have a value of 0.30 or less, 0.28 or less, 0.25 or less, 0.20 or less, or even 0.15 or less;

[0033] Subscript b is the molar ratio of D siloxane units relative to all siloxane units in the organopolysiloxane resin, and has an average value of 0 or more, and may have an average value of 0.10 or more, 0.15 or more, 0.20 or more, or even 0.25 or more, while typically having an average value of 0.35 or less, and may have a value of 0.30 or less, 0.25 or less, 0.20 or less, or even 0.15 or less;

[0034] Subscript c is the molar ratio of T siloxane units relative to all siloxane units in the organopolysiloxane resin, and has an average value of 0.50 or more, and may have an average value of 0.60 or more, 0.70 or more, 0.80 or more, or even 0.90 or more, while typically having an average value of 1.00 or less, or even 0.90 or less, or 0.80 or less, or 0.70 or less, or even 0.60 or less;

[0035] Subscript d is the molar ratio of Q siloxane units relative to all siloxane units in the organopolysiloxane resin, and has an average value of 0 or more, and may have an average value of 0.10 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, or even 0.35 or more, while typically having an average value of 0.50 or less, 0.40 or less, 0.30 or less, 0.25 or less, 0.20 or less, or even 0.15 or less;

[0036] The sum of the subscripts a+b+c+d equals 1.00; and

[0037] The molar ratio of alkyl to aryl groups and the concentration of OZ were as described above for the organopolysiloxane resin 8 / 6.

[0038] It is preferred that the ratio of subscript a / c is in the range of 0 to 0.5, the ratio of subscript b / c is in the range of 0 to 0.5, and the ratio of subscript d / c is in the range of 0 to 0.8.

[0039] The Mw of the organopolysiloxane resin is generally 1,000 or more, preferably 1200 or more, even more preferably 1500 or more, while the Mw is generally 100,000 or less, preferably 10,000 or less, more preferably 5,000 or less.

[0040] Methods for preparing suitable organopolysiloxane resins are well-recognized in the art and generally involve hydrolyzing an organosilane having three hydrolyzable groups (such as halogen or alkoxy groups) on the organosilicon atom in an organic solvent. Suitable organopolysiloxane resins are also commercially available and include those available under the trade names: OWSIL TM RSN-0233 flake resin, DOWSIL RSN-0249 flake resin, DOWSIL RSN-0255 flake resin, DOWSILRSN-6018 resin intermediate, DOWSIL RSN-0805 resin, SILRES TM SY300, SILRES REN168 and SILRES 604. DOWSIL is a trademark of The Dow Chemical Company. SILRES is a trademark of Wacker-Chemie AG.

[0041] Examples of suitable organopolysiloxane resins include any one or any combination of more than one selected from organopolysiloxane resins generally having the following average chemical formula, recognizing that the subscripts are ("Ph" refers to phenyl, "Me" refers to methyl, and "Pr" refers to n-propyl):

[0042] T Ph 70 T Pr 30 , based on the mass of the organopolysiloxane resin, the OZ content is 5.0 mass % OH (36 mol % relative to the moles of the resin), the average Mw is 2,900 g / mol and the molar ratio of alkyl:aryl is 0.43:1;

[0043] D Ph,Me 0.05 D Ph,Ph 0.10 T Me 0.45 T Ph 0.40 , based on the mass of the organopolysiloxane resin, the OZ content is 7.1 mass % OH (46 mol % relative to the moles of the resin), the average Mw is 2,500 g / mol, the molar ratio of alkyl:aryl is 0.77:1, and the ratio of subscript b / c is 0.2;

[0044] DMe,Me 0.15 T Me 0.40 T Ph 0.45 , based on the mass of the organopolysiloxane resin, the OZ content is 6.5 mass % OH (38 mol % relative to the moles of the resin), the average Mw is 3,055 g / mol, the molar ratio of alkyl:aryl is 1.6:1, and the ratio of subscript b / c is 0.2;

[0045] T Ph 1.00 , based on the mass of the organopolysiloxane resin, the OZ content is 8.5 mass % OH (70 mol % relative to the moles of the resin), the average Mw is 2,660 g / mol and the molar ratio of alkyl:aryl is 0:1;

[0046] D Me,Me 0.15 D Ph,Ph 0.05 T Me 0.10 T Ph 0.70 , based on the mass of the organopolysiloxane resin, the OZ content is 6.0 mass % OH (49 mol % relative to the moles of the resin), the average Mw is 3,294 g / mol, the molar ratio of alkyl:aryl is 0.5:1, and the ratio of subscript b / c is 0.3;

[0047] M Me,Me,Me 0.28 T Pr 0.25 T Ph 0.48 , based on the mass of the organopolysiloxane resin, the OZ content is 0.0 mass %, the average Mw is 3,719 / mol, the molar ratio of alkyl:aryl is 2.3:1, and the ratio of subscript a / c is 0.4;

[0048] T Ph 0.65 Q 0.35 , based on the mass of the organopolysiloxane resin, the OZ content is 7.4 mass % OH (38 mol % relative to the moles of the resin), the average Mw is 1,614 g / mol, the molar ratio of alkyl:aryl is 0:1, and the ratio of subscript d / c is 0.5; and

[0049] M Me,Me,Me 0.12 T Ph 0 .53 Q 0.35, based on the mass of the organopolysiloxane resin, the OZ content is 5.2 mass% OH (24 mol% relative to the molar number of the resin), the average Mw is 3,277 g / mol, the molar ratio of alkyl:aryl is 0.68:1, the ratio of subscript a / c is 0.2, and the ratio of subscript d / c is 0.7.

[0050] The concentration of the organopolysiloxane resin in the composition is 10% by mass or more, and may be 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, or even 80% by mass or more, based on the combined mass of (a) the organopolysiloxane resin, (b) the (meth)acrylate component, and (c) the crosslinking agent, while typically being 90% by mass or less, and may be 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, or even 20% by mass or less. If the concentration of the organopolysiloxane resin is insufficient, the cured product does not have adequate adhesion strength and experiences shrinkage greater than 8%. If the concentration of the organopolysiloxane is too high, the cured product is undesirably hard.

[0051] The composition of the present invention further comprises a (meth)acrylate component. The (meth)acrylate component is composed of: (i) at least one monofunctional (meth)acrylate containing ether groups and / or hydroxyl groups; and optionally (ii) at least one monofunctional (meth)acrylate containing an alkyl group and not containing ether groups and hydroxyl groups. The molar ratio of (ii):(i) is 0:1 or greater, and can be 0.2; 1 or greater, 0.5:1 or greater, 1:1 or greater, 2:1 or greater, 3:1 or greater, 4:1 or greater, 5:1 or greater, 6:1 or greater, 7:1 or greater, 8:1 or greater, even 9:1 or greater, and at the same time is typically 22:1 or less, and can be 21:1 or less, 20:1 or less, 19:1 or less, 15:1 or less, 10:1 or less, and can be 9:1 or less, 8:1 or less, 7:1 or less, 6:1 or less, 5:1 or less, 4:1 or less, 3:1 or less, 2:1 or less, 1:1 or less, 0.5:1 or less or even 0.2:1 or less.

[0052] It is expected that the composition of the present invention is cured into an optically transparent material. Monofunctional (meth) acrylates containing ether groups and / or hydroxyl groups are necessary to achieve high light transmittance through the composition once cured. However, it has been surprisingly found that in order to achieve optical transparency, when monofunctional (meth) acrylates containing hydroxyl groups are used for (i), the composition must also contain monofunctional (meth) acrylates containing ether groups and / or monofunctional (meth) acrylates containing alkyl groups and not containing ether groups and hydroxyl groups. Nevertheless, the (meth) acrylate component can include monofunctional (meth) acrylates containing ether groups, which are alone or in combination with monofunctional (meth) acrylates containing hydroxyl groups and or monofunctional (meth) acrylates containing alkyl groups and not containing ether groups and hydroxyl groups and still achieving optical transparency.

[0053] Monofunctional (meth)acrylates containing ether groups and / or hydroxyl groups suitable for use in the (meth)acrylate component include any one compound or any combination of more than one compound selected from the group consisting of (meth)acrylate-functional ethylene glycol, (meth)acrylate-functional propylene glycol, (meth)acrylate-functional polyethers containing poly(ethylene oxide) and / or poly(propylene oxide), and hydroxyl-functional (meth)acrylate-functional compounds.

[0054] Examples of suitable monofunctional (meth)acrylates containing an ether group include methoxyethoxyethyl acrylate, methoxypolyethylene glycol acrylate, methoxypolypropylene glycol acrylate, phenol glycol acrylate, phenol diethylene glycol acrylate, phenol tetraethylene glycol, nonylphenyl glycol acrylate, di(ethylene glycol) 2-ethylhexyl ether acrylate and nonylphenol dipropylene glycol acrylate, 2-(2-ethoxyethoxy)ethyl acrylate; methoxypolyethylene glycol 400 acrylate.

[0055] Examples of suitable monofunctional (meth)acrylates containing a hydroxyl group include hydroxy-substituted (meth)acrylates, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate.

[0056] The monofunctional (meth)acrylate containing an alkyl group and free of ether groups and hydroxyl groups suitable for the (meth)acrylate component may be linear, branched and / or cyclic.

[0057] Examples of the linear alkyl (meth)acrylate containing an alkyl group and not containing an ether group and a hydroxyl group include any one compound or any combination of more than one compound selected from the group consisting of hydroxypropyl butyl acrylate, butyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, ethylhexyl acrylate, n-heptyl acrylate, n-heptyl methacrylate, octyl acrylate, dodecyl acrylate, octyl methacrylate, nonyl acrylate, nonyl methacrylate, lauryl acrylate, lauryl methacrylate, cetyl acrylate, cetyl methacrylate, stearyl acrylate, and stearyl methacrylate.

[0058] Examples of the branched (meth)acrylate containing an alkyl group and not containing an ether group and a hydroxyl group include any one compound or any combination of more than one compound selected from the group consisting of isononyl acrylate, isooctyl acrylate, isooctyl methacrylate, ethylhexyl acrylate, ethylhexyl methacrylate, 2-methylheptyl acrylate, isononyl methacrylate, isobutyl acrylate, isobutyl methacrylate, and isostearyl acrylate.

[0059] Examples of the cyclic (meth)acrylate containing an alkyl group and not containing an ether group and a hydroxyl group include any one compound or any combination of more than one compound selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, cyclohexyl acrylate, dicyclopentanyl acrylate, 2-norbornyl acrylate, and 2-norbornyl methacrylate.

[0060] The concentration of the (meth)acrylate component in the composition is 10% by mass or more, and may be 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, or even 80% by mass or more, based on the combined mass of the (a) organopolysiloxane resin, (b) the (meth)acrylate component, and (c) the crosslinking agent, while typically being 90% by mass or less, and may be 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, or even 20% by mass or less.

[0061] It is desirable that the composition of the present invention is inkjet printable, meaning that it can be printed onto a substrate using an inkjet printing device. To be inkjet printable, the viscosity of the composition must be low enough to work in an inkjet device. To work in an inkjet device, the composition desirably has a viscosity in the range of at least 10 MPa*s at 25°C, while at the same time having a viscosity of 50 MPa*s or less at 60°C. It was discovered as part of the present invention that, to be inkjet printable, the concentration of the organopolysiloxane resin should be in the range of 10% to 60% by mass of the mass of the composition, and at the same time the concentration of the (meth)acrylate component should be in the range of 40% to 90% by mass of the mass of the composition.

[0062] The composition of the present invention also includes a crosslinking agent. The crosslinking agent has an average of at least two ethylenically unsaturated double bonds per molecule. Desirably, at least one of the ethylenically unsaturated double bonds is part of the (meth)acryloyloxy group. The crosslinking agent may contain a blend of unsaturated double bonds that are part of the (meth)acryloyloxy group and unsaturated double bonds that are not part of the (meth)acryloyloxy group. Alternatively, all ethylenically unsaturated double bonds may be part of the (meth)acryloyloxy group. The crosslinking agent provides high temperature stability to the cured composition by crosslinking the composition.

[0063] Suitable crosslinking agents include any one compound or any combination of more than one compound selected from the group consisting of 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, 2-hydroxy-3-methacryloylpropyl acrylate, tripropylene glycol diacrylate, polypropylene glycol diacrylate, pentaerythritol tripropylene glycol diacrylate, acrylates, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, tri(2-acryloyloxyethyl) isocyanurate, caprolactone-modified tri(2-acryloyloxyethyl) isocyanurate, ethoxylated pentaerythritol triacrylate and tetraacrylate, 2-(2-vinyloxyethoxy)ethyl acrylate, 1-(2-vinyloxyethoxy)ethyl methacrylate, and ethoxylated allyl acrylate.

[0064] The concentration of the crosslinking agent component in the composition is 0.1% by mass or more, and may be 0.5% by mass or more, 1.0% by mass or more, 2.0% by mass or more, 3.0% by mass or more, 4.0% by mass or more, 5.0% by mass or more, 6.0% by mass or more, 7.0% by mass or more, 8.0% by mass or more, and even 9.0% by mass or more, based on the combined mass of (a) the organopolysiloxane resin, (b) the (meth)acrylate component, and (c) the crosslinking agent, while typically 11% by mass or less, and may be 10% by mass or less, 9.0% by mass or less, 8.0% by mass or less, 7.0% by mass or less, 6.0% by mass or less, 5.0% by mass or less, 4.0% by mass or less, 3.0% by mass or less, 2.0% by mass or less, and even 1.0% by mass or less. If the concentration of the crosslinking agent is insufficient, the cured product does not have high temperature stability. If the concentration of the cross-linking agent is too high, the cured product becomes undesirably brittle.

[0065] For the avoidance of doubt, the sum of the mass % of the combination of (a) organopolysiloxane resin, (b) (meth)acrylate component and (c) crosslinking agent, based on the combined mass of (a) organopolysiloxane resin, (b) (meth)acrylate component and (c) crosslinking agent, is 100 mass %.

[0066] The composition of the present invention also comprises a photoradical initiator. Suitable photoradical initiators include ultraviolet (UV) initiators, such as any one or any combination of more than one of the following: benzophenone and benzophenone derivatives, acetophenone and acetophenone derivatives, benzoin and its alkyl esters, phosphine oxide derivatives, xanthone derivatives, oxime ester derivatives and camphorquinone. Suitable commercially available photoinitiators include any one or any combination of more than one selected from the following: 2,6-bis(4-azidobenzylidene)cyclohexanone; 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone; 1-hydroxy-cyclohexyl-phenyl-ketone (known under the name OMNIRAD TM184); 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (obtained under the name OMNIRAD 907); 2-hydroxy-2-methyl-1-phenyl-propan-1-one (obtained under the name OMNIRAD 1173); 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (obtained under the name OMNIRAD 2959); methyl benzoylformate (obtained under the name OMNIRAD MBF); α,α-dimethoxy-α-phenylacetophenone (obtained under the name OMNIRAD 651); 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholino)phenyl]-1-butanone (obtained under the name OMNIRAD 369); diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (obtained under the name OMNIRAD TPO); ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate (available under the name OMNIRAD TPO-L); oxime ester compounds (available as products N-1919, NCI-831, NCI-930, NCI-730 and NCI-100 from Adeka Corporation), 12-thioxanthen-9-one; 10-methylphenothiazine; isopropyl-9H-thioxanthen-9-one; 2,4-diethyl-9H-thioxanthen-9-one; 2-chlorothioxanthen-9-one; and 1-chloro-4-propoxy-9H-thioxanthen-9-one. OMNIRAD is a trademark of IGM Group BV.

[0067] The concentration of the photoinitiator in the composition is typically 0.1 mass % or more, and may be 0.5 mass % or more, 1.0 mass % or more, 2.0 mass % or more, 3.0 mass % or more, 4.0 mass % or more, 5.0 mass % or more, 6.0 mass % or more, 7.0 mass % or more, 8.0 mass % or more, or even 9.0 mass % or more, while typically being 10 mass % or less, and may be 9.0 mass % or less, 8.0 mass % or less, 7.0 mass % or less, 6.0 mass % or less, 5.0 mass % or less, 4.0 mass % or less, 3.0 mass % or less, 2.0 mass % or less, or even 1.0 mass % or less, based on the combined mass of the (a) organopolysiloxane resin, the (b) (meth)acrylate component, and the (c) crosslinker.

[0068] The composition of the present invention may optionally include any one component or any combination of more than one additional component, or may not include any one component or any combination of more than one additional component. For example, an additional acrylate monomer having a silicon atom may be present in the composition. Examples of such acrylate monomers include 3-[dimethoxy(methyl)silyl]propyl acrylate, trimethylsilyl methacrylate, trimethylsilyl acrylate, triisopropylsilyl acrylate, 3-(methoxydimethylsilyl)propyl acrylate, (trimethoxysilyl)methyl methacrylate, 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-(tri(trimethylsilyloxy)silyl]propyl methacrylate, and methacryloyloxypropyl(tri(trimethylsilyloxy)silyl)propyl) The concentration of the additional acrylate monomer is typically 10% by mass or less, and may be 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, 2% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, or even 0.1% by mass or less, based on the combined mass of the (a) organopolysiloxane resin, the (b) (meth)acrylate component, and the (c) crosslinking agent, and may be 0% by mass.

[0069] The composition may or may not contain a free radical scavenger. It may be desirable for the free radical scavenger to extend the storage stability of the composition by inhibiting curing until the composition is intentionally exposed to UV light. Free radical scavengers include phenolic compounds, such as any one or more than one combination of 4-methoxyphenol (MEHQ, methyl ether of hydroquinone), hydroquinone, 2-methylhydroquinone, 2-tert-butylhydroquinone, tert-butylcatechol, butylated hydroxytoluene, and butylated hydroxyanisole. Other types of free radical scavengers include phenothiazines and anaerobic inhibitors, such as NPAL type inhibitors (tris-(N-nitroso-N-phenylhydroxylamine) aluminum salts) available from Albemarle Corporation. Typically, the free radical scavenger is present in the composition at a concentration of 0 mass % or greater, 0.001 mass % or greater, 0.01 mass % or greater, or even 0.5 mass % or greater, while typically being present at a concentration of 1.0 mass % or less, and may be present at a concentration of 0.5 mass % or less, or even 0.1 mass % or less, wherein the mass % is based on the combined mass of the (a) organopolysiloxane resin, (b) (meth)acrylate component, and (c) crosslinking agent.

[0070] The composition of the present invention may or may not contain a plasticizer. A plasticizer is a non-reactive component that reduces the viscosity of the composition when added to the composition. Desirably, the composition does not contain a plasticizer.

[0071] The composition may or may not contain any one or any combination of more than one other additional additives, including those selected from UV absorbers, antioxidants, sensitizers (e.g., anthracene derivatives and acridine derivatives) and chain transfer agents. These other additional additives may be present at a combined concentration of 0 mass % or greater, 0.001 mass % or greater, 0.01 mass % or greater, or even 0.5 mass % or greater, while typically present at a concentration of 1.0 mass % or less, and may be present at a concentration of 0.5 mass % or less, or even 0.1 mass % or less, wherein the mass % is based on the combined mass of (a) the organopolysiloxane resin, (b) the (meth)acrylate component, and (c) the crosslinking agent.

[0072] The present invention also includes a method for using the composition of the present invention. The composition of the present invention can be used as an adhesive material, desirably an inkjet printable and / or optically transparent adhesive. In this regard, a method of the present invention for using the composition as an adhesive, wherein the method includes the steps of applying the composition to a first object, and then applying a second object to the composition so that the composition is sandwiched between the first object and the second object and in contact with the first object and the second object.

[0073] The composition of the present invention is UV curable. Desirably, the method of the present invention further comprises curing the composition between the first object and the second object by exposing the composition to ultraviolet light.

[0074] It is desirable to pre-cure the composition after being applied to the first object and before applying the second object. Pre-curing is to partially cure the composition by, for example, exposing the composition to UV light sufficient to partially cure the composition. Pre-curing can establish the viscosity of the composition, which may be desirable when the composition has a low viscosity (such as may be desirable for inkjet printing compositions), but then a higher viscosity is desired to prevent the composition from undesirably flowing once applied to the first object. For example, the composition may require a relatively low viscosity to flow easily during application to the first object, but the first object may need to be reoriented (such as inverted) in order to apply the second object, and it may be undesirable for the composition to flow on the first object during re-orientation. Pre-curing can establish viscosity in the composition before re-orientation to prevent flow during re-orientation, but makes the fully uncured composition have enough softness and conformability to be tightly bonded to the second object without gaps. The degree of pre-curing can be controlled by changing the UV light intensity and / or irradiation time used in the pre-curing. Increasing any of these will increase the degree of pre-curing. If the degree of pre-cure is too low, the pre-cured composition is too easily deformed and can be squeezed out from between the first object and the second object when pressed between the first object and the second object. If the degree of pre-cure is too high, the composition is not deformed enough to conform to the first object and the second object and a void between the composition and at least one object results. If the pre-cure is too high, the composition may also suffer from poor adhesion to one or both substrates.

[0075] Desirably, the pre-curing results in a degree of cure in the composition of 50% or greater, and may be 70% or greater, 75% or greater, 80% or greater, or even 90% or greater, while at the same time being 100% or less, and may be 90% or less, 80% or less, 70% or less, or even 60% or less.

[0076] Fourier transform infrared (FTIR) spectroscopy was used to monitor the infrared spectrum of the composition at 809 or 1408 wavenumbers (cm -1 The degree of curing is determined by the absorption peak intensity of the unsaturated double bond (C=C) appearing at 809 cm -1 peak, but if this peak is too difficult to resolve, use 1408cm -1 The peaks at these locations decrease in intensity with the degree of cure, since curing involves reacting unsaturated double bonds and thereby consuming them. The degree of cure is calculated using the following equation:

[0077] Curing degree (%) = 100% [(Ao-Ai) / Ao]

[0078] in:

[0079] Ai = absorption peak intensity of unsaturated double bonds in the composition after UV irradiation; and

[0080] Ao = absorption peak intensity of unsaturated double bonds in the composition before UV irradiation.

[0081] In the widest range of the inventive method, the composition can be applied to the first object by any means. For example, the following devices are suitable for applying the composition to the first object: gravure coaters, offset coaters, offset gravure coaters, roll coaters, reverse roll coaters, and printing methods such as screen printing, pin transfer, stencil printing, and inkjet printing. Desirably, the composition is inkjet printed onto the first component using an inkjet printer in a desired pattern.

[0082] The first object and / or the second object may transmit optical light and may be optically transparent. Desirably, at least one of the first object and the second object transmits UV light, and curing of the composition is performed by exposing the composition to UV light passing through at least one of the first object and the second object after applying the second object.

[0083] Desirably, UV pre-curing and curing of the composition is performed using any one wavelength selected from 365 nanometers (nm), 385 nm, 395 nm and 405 nm or a combination of more than one wavelength. For optimal control of UV exposure, it is beneficial to use a UV light emitting diode (LED) lamp. Typically, the UV light exposure dose is 0.1 joule / square centimeter (J / cm 2 ) or more, and can be 1.0 J / cm 2 or greater, while typically 200 J / cm 2 or less, and can be 100 J / cm 2 or less. UV exposure of the composition to cure the composition can be carried out in air. However, oxygen can inhibit curing, so UV exposure can be preferably carried out in an oxygen-free atmosphere (such as in nitrogen or carbon dioxide).

[0084] Example

[0085] Table 1 lists the components used to prepare the Examples (Ex) and Comparative Examples (C Ex) in this section. "Ph" refers to phenyl, "Me" refers to methyl, "Pr" refers to n-propyl, and "Ma" refers to methacryloxypropyl. The "a / c", "b / c" and "a / d" ratios refer to the ratios with subscripts of those letters as used in Formula (I).

[0086] Table 1

[0087]

[0088]

[0089]

[0090] DOWSIL is a trademark of The Dow Chemical Company. OMNIRAD is a trademark of IGM Group B.V. Besloten Vennootschap.

[0091] Preparation of A-6

[0092] A 500 ml (mL) three-necked flask was equipped with a thermometer, a dean-stark trap and a reflux condenser. 158.02 g of A-1 was added to the flask and dissolved in 80.02 g of toluene. Once dissolved, 54.01 g of hexamethyldisilazane (Sigma-Aldrich) and 0.12 g of trifluoroacetic acid (Sigma-Aldrich) were slowly added to the flask. The resulting mixture was stirred for one hour at 40 degrees Celsius (°C). 25.65 g of water was added to the mixture and the temperature was slowly raised to reflux temperature and maintained for 2 hours. Water and by-products were removed by azeotropic distillation through the dean-stark trap. The solution was cooled to 25°C. Filtered and toluene was removed under reduced pressure to obtain A-6.

[0093] Preparation of A-7

[0094] 200mL four-necked flask is equipped with mechanical stirrer, thermometer, dropping funnel and reflux condenser.Add 24.17g trimethoxyphenylsilane (Sigma Aldrich) and 13.67g tetraethyl orthosilicate (Sigma Aldrich).Slowly add 1.66g concentrated hydrochloric acid and 12.15g water while stirring the mixture in the flask.Stir for 2 hours, and then add 25g toluene.Treat the resulting mixture with 25g toluene and 50g water, and transfer to a separating funnel.Collect and merge the bottom and top of the three layers of gained, and wash with 50g water.Collect the top and bottom of the 3 layers of gained again, and repeat washing three times.Separate the organic layer and dry over anhydrous sodium sulfate, and then filter to obtain 21% A-7 solution.

[0095] Preparation of A'-8

[0096] 200mL four-necked flask is equipped with mechanical stirrer, thermometer, dropping funnel and reflux condenser.Add 1.98g hexamethyldisiloxane (Sigma Aldrich), 21.35g trimethoxyphenylsilane (Sigma Aldrich) and 14.81g tetraethyl orthosilicate (Sigma Aldrich).Slowly add 1.66g concentrated hydrochloric acid and 11.85g water while stirring the mixture in the flask.Stir 2 hours, and then add 25g toluene.Treat the resulting mixture with 25g toluene and 50g water, and transfer to a separating funnel.Collect and merge the bottom and top of the three layers of gained, and wash with 50g water.Collect the top and bottom of the 3 layers of gained again, and repeat washing three times.Separate the organic layer and dry over anhydrous sodium sulfate, and then filter to obtain 23% A'-8 solution.

[0097] Preparation of A'-10

[0098] A 200 mL four-necked flask was equipped with a mechanical stirrer, a thermometer, a dropping funnel and a reflux condenser. 26.97 g of trimethoxyphenylsilane (Sigma Aldrich) and 11.26 g of OFS-6030 were added. 1.66 g of concentrated hydrochloric acid and 11.75 g of water were slowly added while the mixture in the stirring flask. Stir for 2 hours, and then 25 g of toluene was added. The resulting mixture was treated with 25 g of toluene and 50 g of water, and transferred to a separating funnel. The bottom and top of the three layers were collected and combined, and washed with 50 g of water. The top and bottom of the 3 layers were collected again, and the washing was repeated three times. The organic layer was separated and dried over anhydrous sodium sulfate, and then filtered to obtain a 42% A'-10 solution.

[0099] Sample composition

[0100] Tables 2 to 4 list the compositions of the Example (Ex) and Comparative Example (C Ex) compositions, where the component amounts are listed in grams. Tables 5 and 6 list the characterization of the compositions, including the cured form of the compositions.

[0101] For C Ex A to C Ex K, component (B), component (C) and component (D) are mixed with a stirrer for one minute at 23° C. For example, C Ex A is prepared by combining 99 g of component [B(i)-a1], 1 g of component (C-1) and 0.5 g of component (D-1), and then mixing them together with a stirrer at 23° C. for one minute.

[0102] For C Ex L to C Ex T, Ex 1 to Ex 27 and Ex 31, the A component (A-1, A-2, A-3, A-4, A-5, A-6, A'-9, A'-11 or A'-12) is dissolved in the (B) component. Then, the component (C) and the component (D) are added to the resulting solution and mixed. For example, Ex. 1 is prepared by dissolving 50.2 g of the component (A-1) in 5.6 g of the component [B(i)-a1] and 43.2 g of the component [B(i)-a1] while stirring at 23° C. for 24 hours. Then, 1.0 g of the component (C-1) and 0.5 g of the component (D-1) are added to the solution and mixed with a stirrer at 23° C. for one hour.

[0103] For C Ex U to C Ex V and Ex 28 to Ex 29, the A component (A-7, A-8 or A'-10) which is already a solution in an organic solvent is dissolved in component (B). Then, the organic solvent is removed under reduced pressure at 40°C to 80°C. Cool to 23°C, add component (C) and component (D) to the solution and mix. For example, to prepare Ex 28, 313.3g of 21% A-7 solution (65.8g A-7) and 33.2g [B(i)-a2] are combined in a 1 liter flask. Then, the organic solution is removed by a rotary evaporator (at 50°C, <1 torr for 6 hours) under nitrogen bubbling. Cool to 23°C, and then add 1.0g of component (C-6), 1g of component (D-1) to the above mixture, and mix with a stirrer for one hour at 23°C.

[0104] Each sample was characterized using the following characterizations:

[0105] Viscosity

[0106] The viscosity (dynamic viscosity) of each sample was measured using an AR-G2 rheometer with a 40 mm diameter 2-degree cone-plate measuring system. -1 The shear rate was 1000 μm for one minute. The sample temperature was controlled using a Peltier plate.

[0107] Shear storage modulus

[0108] Test samples of each sample composition were cured to test the shear storage modulus. The sample composition was poured into a mold (1 millimeter (mm) thick×50 mm wide×50 mm long) and sandwiched between fluorine-coated polyethylene terephthalate films. The sample composition in the mold was exposed to 365 nm wavelength LED light (FireJet TMFJ100 lamp; FireJet is a trademark of Phoseon Technology, Inc.) with 6J / cm 2 The sample composition was cured with a total UV dose of . After curing the sample composition, the fluorinated polyethylene terephthalate film was removed and the cured sample was mounted on a parallel plate geometry (25 mm) of a rheometer (AtonParr MCR-502). Shear storage modulus (G') was collected at a fixed frequency of 1 Hz at 25°C and 80°C with a strain of 1.0% and a normal force of 0.5 Newton. G' is reported in kilopascals (kPa).

[0109] Transmittance

[0110] The sample composition was poured into a mold (1 mm thick × 50 mm wide × 50 mm long) and sandwiched between microslide glasses (Matsunami Glass Co., Ltd. Product No. 9213). The sandwiched sample composition mold was exposed to 365 nm wavelength LED light (FireJet TM FJ100 lamp; FireJet is a trademark of Fengxiang Technology Co., Ltd.) with 6J / cm 2 The interlayer sample composition mold was cured with a total UV dose of . The transmittance of the 550 nm wavelength through the cured sample composition was measured according to ASTM method D1003 (using a UV-visible spectrophotometer, Konica Minolta CM-3600A, and the reference material was deionized water). The transmittance through the cured sample material was referenced to the transmittance through deionized water to determine %T.

[0111] Peel Adhesion Strength

[0112] The sample composition was coated onto a glass plate to form a 40 micron film (100 mm wide and 150 mm long) and exposed to 1.5 J / cm 2 The film was pre-cured with 365 nm light from an LED lamp (FireJet FJ100). A corona treated polyethylene terephthalate film was placed on the pre-cured film and bonded to the pre-cured film by moving a 2 kg mass rubber line roller back and forth over the film twice. The film was then pre-cured by applying 5 J / cm 2The resulting laminate was fully cured by irradiation with 365 nm light from an LED lamp at an exposure of 1000 nm. The cured laminate was aged for one day at 25 ° C. The PET layer was cut through to form a 2.54 cm wide PET film strip on the cured composition film. Using a texture analyzer, the PET film was peeled off from the cured composition film by pulling along the length of the PET film strip at a speed of 5.0 mm / sec at an angle of 180 ° relative to the initial orientation of the PET film. Adhesion strength is reported in Newtons per meter (N / m).

[0113] Shrinkage

[0114] The specific gravity (SG) of the sample composition was measured using the gravimetric cup method at 25°C. L The sample composition was poured into a mold (10 mm thick, 20 mm wide and 40 mm long) and sandwiched between fluorine-coated polyethylene terephthalate films. The sample composition was exposed to 365 nm wavelength LED light (FireJet TM FJ100 lamp; FireJet is a trademark of Fengxiang Technology Co., Ltd.) with 6J / cm 2 The sample composition was cured by a total UV dose of . The fluorine-coated polyethylene terephthalate film was removed and the specific gravity (SG) of the cured film was measured according to the test method JIS K7112 B. S ). The total shrinkage of the cured composition is determined as a percentage relative to the pre-cured sample and is calculated as follows:

[0115] % Shrinkage = 100% × [(SG S )-(SG L )] / (SG L )

[0116] result

[0117] Examples (Ex) 1 to 29 are examples of photocurable silicone acrylate compositions of the present invention that provide flowable liquids having a viscosity of 14 millipascals*seconds (MPa*s) to 27,000 MPa*s at 25° C. and 2 mPas*s to 4453 mPas*s at 60° C. before curing. When the composition is cured using ultraviolet (UV) light, the composition is optically clear (%T greater than 90% at 1 mm thickness) and has a shear storage modulus (G) greater than 1 kPa and less than 1157 kPa at 25° C. and greater than 1 kPa and less than 500 kPa at 80° C., a peel adhesion strength in the range of 65 Newtons / meters (N / m) to 1160 N / m (170 gf / inch to 3000 gf / inch), and a shrinkage of less than 8%. Of particular importance are those samples having a viscosity of at least 10 MPa*s at 25°C and at the same time a viscosity of 50 MPa*s or less at 60°C (Examples 1 to 3, 5 to 20, 22, 23, 25 to 27, 30 and 31), as those samples are suitable for application by an inkjet method.

[0118] Comparative Examples (C Ex) A, C Ex C, C Ex D, C Ex G, and C Ex I illustrate that photocurable silicone compositions containing all components of the presently claimed composition except the organopolysiloxane resin result in undesirable adhesion strength and shrinkage.

[0119] C Ex B and C Ex F illustrate that the photocurable silicone composition containing all components of the presently claimed composition except the organopolysiloxane resin results in undesirable shrinkage.

[0120] C Ex E, C Ex H, C Ex J, and C Ex K illustrate that the photocurable silicone composition containing all components of the presently claimed composition except the organopolysiloxane resin results in undesirable adhesion strength.

[0121] C Ex L and C Ex S illustrate that the photocurable silicone composition containing all the components claimed in the present invention except the monofunctional (meth)acrylate containing ether groups and / or hydroxyl groups cannot achieve optical transparency.

[0122] C Ex M to C Ex R illustrate that when the molar ratio b(ii) / b(i) is higher than 25, the photocurable silicone composition containing all the components claimed in the present invention cannot achieve optical transparency (transmittance is lower than 90%).

[0123] C Ex T illustrates that the photocurable composition using MQ resin as the organopolysiloxane resin produces a cured sample that has poor transmittance and is not optically clear.

[0124] C Ex U and C Ex V illustrate the use of a material having at least 50 mol% R 1 SiO 3 / 2 Unit (where R 1 Photocurable compositions containing methacryloyloxypropyl functional T units and an organopolysiloxane resin selected from alkyl and aryl groups, produced cured samples with no adhesion strength. Without being bound by theory, one possibility is that the resin cures too hard, has too high a shear storage modulus and does not have enough tack to obtain sufficient adhesion strength because the (meth)acryloyl functional silicone resin increases the crosslink density. Therefore, it is important to use alkyl and aryl groups (which are by definition non-functional in these crosslinking reactions) as the R of the organopolysiloxane resin. 1 SiO 3 / 2 Unit R 1 Group.

[0125] C Ex W and C Ex X illustrate the use of less than 50 mol% R 1 SiO 3 / 2 Unit (where R 1 A photocurable composition using an organopolysiloxane resin selected from an alkyl group and an aryl group) and using an organopolysiloxane resin having a Mw of less than 1000 g / mol produced a cured sample without the desired adhesion strength.

[0126] Ex 1 illustrates that, particularly relative to C Ex L, inclusion of the claimed organopolysiloxane resin component in the composition of C Ex A produces a composition that cures to an optically clear material, has a desired adhesion strength and shrinkage, while having a desired viscosity prior to cure. Comparison of Ex 1 and Ex 7 with C Ex L and C Ex S illustrates the importance of monofunctional acrylates containing ethers and / or hydroxyls to achieve optical clarity. Comparison of Comparative Examples 1, 2, and 7 to 11 with Comparative Examples M to R illustrates that the compositions of the present invention can achieve a transmittance greater than 90% at 550 nm while also having a molar ratio of b(ii):b(i) in the range of 0:1 to 18:1. Molar ratios of b(ii):b(i) in the range of 0:1 to 22:1 are expected to produce optically clear materials.

[0127] Examples 3, 4, 14, 24, 25, and 28 to 30 specifically illustrate that the composition of the present invention can be cured into an optically transparent material having desired adhesion even without a monofunctional (meth)acrylate containing an alkyl group and not containing an ether group or a hydroxyl group.

[0128] Ex 3 and Ex 4 as well as Ex 9 and Ex 11 illustrate that increasing the concentration of the organopolysiloxane resin tends to increase the adhesion strength of the resulting cured composition.

[0129] Ex 20 to Ex 30 illustrate that the photocurable silicone acrylate composition of the present invention is cured with a variety of different organopolysiloxane resin components to form an optically transparent material having desired properties, provided that R 1 SiO 3 / 2 The amount of units is at least 50 mol% of the siloxane units and each R 1 Although the organopolysiloxane resin may contain M, D and Q siloxane units, R 1 SiO 3 / 2 Unit (where R 1 The groups selected from alkyl and aryl groups) must be at least 50 mol% of the siloxane units.

[0130] The specific selection of the organopolysiloxane resin also appears to reduce shrinkage of the curable composition upon curing.

[0131] Notably, none of these embodiments include a plasticizer.

[0132]

[0133]

[0134] Table 4

[0135]

[0136] Table 5

[0137]

[0138] Table 6

[0139]

Claims

1. A composition comprising the following components: (a) 10 to 90 mass % of an organopolysiloxane resin containing at least 50 mol % of T siloxane units, wherein the molar ratio of alkyl groups to aryl groups in the organopolysiloxane resin is in the range of 0:1 to 4:1; (b) 10% to 90% by mass of a (meth)acrylate component, the (meth)acrylate component consisting of: (i) at least one monofunctional (meth)acrylate containing ether groups and / or hydroxyl groups; and Optional (ii) at least one monofunctional (meth)acrylate containing an alkyl group and containing no ether group and no hydroxyl group; wherein the molar ratio of (ii) to (i) is in the range of 0:1 to 22:1, and wherein when the (meth)acrylate component comprises a monofunctional (meth)acrylate containing a hydroxyl group, It further comprises at least one monofunctional (meth)acrylate containing an ether group as part of component (i) and / or a monofunctional (meth)acrylate containing an alkyl group and not containing an ether group and a hydroxyl group as part of component (ii); (c) 0.1 to 11 mass % of a cross-linking agent having an average of at least two ethylenically unsaturated double bonds per molecule; and (d) 0.1 to 10% by mass of a photoradical initiator; Wherein the mass percentages are relative to the combined mass of component (a) to component (c), and wherein the mass percentages of component (a) to component (c) add up to 100 mass %.

2. The composition according to claim 1, wherein the concentration of component (a) is 10% to 60% by mass, and the combined concentration of component (b) and component (c) is 40% to 90% by mass, relative to the combined mass of components (a) to (c).

3. A composition according to claim 1 or claim 2, wherein component (a) has an average chemical composition (I): M a D b T c Q d (I) in: Subscript a is the molar ratio of the M siloxane units relative to the number of moles of all siloxane units and has an average value ranging from 0 to 0.35; Subscript b is the molar ratio of the D siloxane unit relative to the number of moles of all siloxane units and has an average value ranging from 0 to 0.35; Subscript c is the molar ratio of the T siloxane unit relative to the number of moles of all siloxane units and has an average value ranging from 0.50 to 1.00; Subscript d is the molar ratio of the Q siloxane unit relative to the number of moles of all siloxane units and has an average value ranging from 0 to 0.50; The sum of the subscripts a+b+c+d equals 1.00; The molar ratio of alkyl to aryl is in the range of 0:1 to 4:1; The concentration of the OZ group is in the range of 0 mol % to 100 mol % based on the moles of the organopolysiloxane resin; and The ratio of subscript a / c is in the range of 0 to 0.5, the ratio of subscript b / c is in the range of 0 to 0.5; and the ratio of subscript d / c is in the range of 0 to 0.

8.

4. A composition according to any preceding claim, wherein component (b)(i) is one or a combination of more than one compounds selected from the group consisting of (meth)acrylate-functional ethylene glycol, (meth)acrylate-functional propylene glycol, (meth)acrylate-functional polyethers comprising a plurality of ethylene oxide and / or propylene oxide units, and hydroxy-functional (meth)acrylate-functional compounds.

5. A composition according to any preceding claim, wherein component (c) is a compound comprising an average of at least two ethylenically unsaturated double bonds, wherein at least one of the ethylenically unsaturated double bonds is part of a (meth)acryloyloxy group.

6. A composition according to any preceding claim, wherein the composition is free of plasticizers.

7. A method comprising using a composition according to any preceding claim as an adhesive, the method comprising the steps of: The composition is applied to a first object, and then a second object is applied to the composition so that the composition is sandwiched between and in contact with the first object and the second object.

8. The method of claim 7, further comprising curing the composition by exposing the composition to ultraviolet light while the composition is between and in contact with the first object and the second object.

9. The method of claim 7 or claim 8, further comprising pre-curing the composition by exposing the composition to ultraviolet light after applying the composition to the first object and before applying the second object to the composition.

10. The method according to any one of claims 7 to 9, wherein the composition is the composition according to claim 2, and the composition is applied to the first object using an inkjet method.